المقاربات النقدية في تطوير مناهج تعليم اللغة العربية للناطقين بها: Critical Approaches to Developing Arabic Language Curricula for Native Speakers (Al-Qamar, 2025)
This paper explores the discursive dynamics of critical pedagogy as a postmodern approach to language learning, with a particular focus on Arabic instruction. Critical pedagogy emphasizes the interrelationship between educational practices and broader social contexts, aiming to cultivate learners’ critical thinking skills and empower them as agents of change. Rooted in the foundational principles of the Frankfurt School—particularly its tradition of social critique that emerged in Germany in 1923—this theoretical framework finds a key expression in Paulo Freire’s concept of dialogic pedagogy, which underscores the centrality of dialogue in the learning process. In the absence of such dialogic and critical engagement, language education risks becoming rigid and unreflective. In the American context, critical pedagogy is closely associated with the work of Henry Giroux, who further developed its application in contemporary educational theory. This study employs a qualitative research method using a library-based approach to examine relevant literature and theoretical discourse surrounding critical pedagogy. The findings underscore the importance of integrating critical pedagogy into Arabic language instruction to foster critical reasoning, enabling learners to resist ideological orthodoxy and orthopraxy embedded in some learning materials. Applying Critical Pedagogy to Improve the Teaching of Arabic as a Foreign Language.
Keywords: Arabic language, curricula, critical approaches, native speakers